Economy Digitalization under the wave Nature of Innovation Development - R. M. Nureev; O. V. Kаrapaev (Управленческие науки)
The paper is devoted to the consideration of approaches to the study of innovative development frequency and some aspects of the ongoing economy digitalization. The research methodology is based on the innovation theory and the evolutionary theory of economic change. The study was performed using comparative analysis, abductive and inductive methods. The authors proposed to determine the list of technologies of Industry 4.0 based on their influence on the development of the digital economy key factor — digital data. The realization examples of the J. A. Schumpeter’s creative destruction concept by mean of technologies integration that are the basis of the economy digitalization are stated. During the consideration of the innovative context of the economy digitalization, the interrelation of the general patterns of development between the nature of the changes in technological stages in economy and direct natural selection of biological creatures is shown. Having based on the study authors recommend to prioritize the development and / or implementation of the third component of the digital economy, advanced digital technologies, in conformity with the functions they allow to perform extracting the value from digital data. The study may be of interest to government agencies, commercial and international organizations. The practical significance of the study for government agencies, commercial and international organizations consists of the possibility of building strategic and tactical plans for digital development and recording the digitalization results in the context of technologies related to each of the four stages of extracting value from digital data.